Respuesta :

Step-by-step explanation:

"b2"   was replaced by   "b^2".  1 more similar replacement(s).

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

                    a-((h*(b^2+b^2))/(2))=0

     

Simplify: hb2 /1

a -  hb2  = 0

Factoring:  a-hb2

Theory : A difference of two perfect squares,  A2 - B2  can be factored into  (A+B) • (A-B)

(A+B) • (A-B) =

 A2 - AB + BA - B2 =

 A2 - AB + AB - B2 =

 A2 - B2

AB = BA is the commutative property of multiplication.

- AB + AB equals zero and is therefore eliminated from the expression.

a1   is not a square

Binomial can not be factored as the difference of two perfect squares

a - hb2  = 0

Solve :a-hb2  = 0

I think